2018
DOI: 10.1007/s10815-018-1196-3
|View full text |Cite
|
Sign up to set email alerts
|

One-year impact of bariatric surgery on serum anti-Mullerian-hormone levels in severely obese women

Abstract: This pilot study shows a drastic reduction in AMH levels at 1 year after BS in reproductive-age severely obese women, which was not related to weight loss: this suggests a negative impact of BS on ovarian reserve, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
4
14
0
Order By: Relevance
“…Importantly, the reported AMH decrease was not associated with subfertility in post-bariatric women. The post-bariatric decrease in AMH could be linked with malnutrition, however, no relationship between AMH and nutritional deficiencies was found ( Vincentelli et al , 2018 ). The AMH decrease could reflect a decreased ovarian reserve, although it is unknown how bariatric surgery should affect the ovarian follicle pool.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the reported AMH decrease was not associated with subfertility in post-bariatric women. The post-bariatric decrease in AMH could be linked with malnutrition, however, no relationship between AMH and nutritional deficiencies was found ( Vincentelli et al , 2018 ). The AMH decrease could reflect a decreased ovarian reserve, although it is unknown how bariatric surgery should affect the ovarian follicle pool.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has a significant impact on reproductive health, as excess body weight is the main cause for ovulatory infertility 30 . Recent studies have shown serum AMH level was increasingly being recognized as the most important biomarker for ovarian reserve and was used to counsel patients regarding in their reproductive outcomes 6,9,31 . Although the relationship of AMH and obesity has been described before, findings of these studies are controversial.…”
Section: Pcos Shares Many Similarities With Ms In Clinical Features and Pathophysiologymentioning
confidence: 99%
“…It plays a mediator role particularly in the development of primordial follicles and the selection of follicles 7 . Since serum AMH levels are proportional to the number of developing follicles in the ovaries and it differs only slightly during the menstrual cycle, serum concentration of AMH in females may represent both the quality and quantity of the ovarian follicle pool 8,9 . The large amount of data has showed that AMH levels are generally much higher in women with PCOS than in normal women.…”
Section: Introductionmentioning
confidence: 99%
“…AMH levels were measured before and 6 and 12 months after surgery. A strong decrease in AMH values was detected 12 months after surgery without a relation with loss in weight and the authors of the study postulated a negative influence of surgery on the ovarian reserve [ 35 ]. They hypothesized that postoperative stress of growth follicles in ovaries may be the reason for the reduction in AMH values, indicating the need for prolonged observational studies in order to clarify observed changes.…”
Section: Bariatric Surgery and Obesitymentioning
confidence: 99%